Recent Evolution of Public Sector Structure in Latin America: Describing and Explaining Shifts in Autonomy Trends in Colombia and Venezuela. (February 2016) - González, Camilo Ignacio; Verhoest, Koen
Summary: This article has two objectives. The first objective is to review and assess the recent evolution of agency design in Colombia and Venezuela. More specifically, we study the agencies' formal autonomy in these two countries since the year 1999 when Venezuela experienced a major change in government policy towards socialism. Thus, we attempt to explore how this policy change is reflected in the formal autonomy of agencies. Our second objective is to test if, despite the differences in policy choices the two countries have taken in the recent years, there are theoretical factors related to the agencies' design that can explain the level of formal autonomy of the agencies. The results show two main elements: first, even though the patterns of formal agency autonomy in Colombia and Venezuela differed before Venezuela's latter policy change, the differences between these two countries have increased since 2000. This indicates that each country's policy preferences may account for the differences. Second, for both countries, we found that, despite the differences, agency level factors such as the primary tasks that are performed by the agencies and the policy sector in which they are active have had an impact on their level of formal autonomy. However, the results indicate that these relationships do not follow the predictions that have been made based on the different theoretical perspectives. Copyright © 2016 John Wiley & Sons, Ltd.